SCIENTIFIC AND METHODOLOGICAL FOUNDATIONS FOR DEVELOPING WRITING SKILLS OF LOW-PROFICIENCY ENGLISH LEARNERS IN VOCATIONAL COLLEGES (International Congress on Economics, Management and Business Studies, 2026)
This article analyzes the challenges of developing writing skills among vocational college students with low proficiency in English. It highlights the role of psycholinguistic approaches, communicative methods, and modern pedagogical technologies in the formation of written speech.
Keywords: Writing skills, English language, vocational college, communicative approach, individualized instruction, methodology.